Hedonis Lifestyle on Impulse Buying Behavior Monzer Kahf Islamic Consumption Perspective - Sulistyowati Sulistyowati; Alvy Zainuna (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
Hedonic is a lifestyle of an individual to spend time having fun. This lifestyle triggers impulse buying behavior which is included in consumptive behavior. This study aims to answer the questions of how hedonic lifestyles affect impulse buying behavior and how hedonic lifestyles affect impulse buying behavior from the Islamic consumption perspective of Monzer Kahf. The type of research is field research which focuses on a case study. The research location is at PP Al-Fath Kediri. This research uses a qualitative approach. Data sources come from primary and secondary data collected through observation, interviews, and documentation. The validity of the data is carried out by increasing the accuracy of the research, using reference sources, triangulation, and conducting member checks. The results of this study indicate that (1) Students who live at PP Al-Fath prefer to spend their free time shopping online because they are considered more flexible. This is included in the hedonic lifestyle that can trigger impulse buying behavior. (2) The hedonic lifestyle of the impulse buying behavior of PP Al-Fath students contradicts the consumption theory expressed by Monzer Kahf, which includes rationalism and the concept of goods in Islam.